PENGAWASAN STANDAR ANGKUTAN LAUT DI KOTA PEKANBARU - Winarni, Sri; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
One of the objectives of this study is to determine the extent of supervision of sea transport standards in Pekanbaru City. Sea transportation is one of the means of transportation as a form of service to the community to make it easier to travel from one place to another through the waters. In realizing safe, safe, fast, smooth, orderly and orderly transportation, comfortable and efficient, there needs to be supervision from KSOP (Office of Port Authority and Port Authority) Pekanbaru through the Traffic Section of Sea Transportation and Ports Business by deploying Kaposker (Head of Post Work) and its members. However, the surveillance carried out has not yet fully gone well. This is due to the condition of ships that are not in accordance with sea transport passenger service standards on board and the obligation of the Kaposker to provide supervision reports every day is not carried out properly, causing the KSOP Pekanbaru vision to realize the Safe, Comfortable and Safe Sea Transportation Service. The researcher uses the concept of Manullang theory (2015: 184) which is to set measurement tools (standards), deal with assessments, and take corrective actions using qualitative research methods, using Purposive Sampling techniques for selecting informants and conducting data collection techniques through observation, interviews, documentation and triangulation. The results of the study showed that the Supervision of Sea Freight Standards in Pekanbaru City was related to the Passenger Sea Freight Services Standards that were not fully operational. This is because there are obstacles Lack of Legal Awareness of the Government, Operators and users of transportation services. Keywords: Supervision, Service Standards, Transportation